2014
DOI: 10.1094/cchem-09-13-0198-r
|View full text |Cite
|
Sign up to set email alerts
|

Bran Characteristics and Bread‐Baking Quality of Whole Grain Wheat Flour

Abstract: Cereal Chem. 91(4): [398][399][400][401][402][403][404][405] Variations in physical and compositional bran characteristics among different sources and classes of wheat and their association with breadbaking quality of whole grain wheat flour (WWF) were investigated with bran obtained from Quadrumat milling of 12 U.S. wheat varieties and Bühler milling of six Korean wheat varieties. Bran was characterized for composition including protein, fat, ash, dietary fiber, phenolics, and phytate. U.S. soft and club whea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
2
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 32 publications
2
39
2
4
Order By: Relevance
“…Extended mixing time is generally required to produce optimally developed dough with an increase in water absorption (Cai et al, 2014b). Increases of 5 to 6% in the water absorptions of WWFs were observed with hydration of bran to 60% moisture for both hard red and hard white wheat regardless of bran particle size.…”
Section: Effects Of Bran Pre-hydration On Bread-baking Quality Of Wwfmentioning
confidence: 99%
“…Extended mixing time is generally required to produce optimally developed dough with an increase in water absorption (Cai et al, 2014b). Increases of 5 to 6% in the water absorptions of WWFs were observed with hydration of bran to 60% moisture for both hard red and hard white wheat regardless of bran particle size.…”
Section: Effects Of Bran Pre-hydration On Bread-baking Quality Of Wwfmentioning
confidence: 99%
“…Although wheat is used primarily as a source of energy, whole wheat grain is an excellent source of dietary fiber, minerals, vitamins, and bioactive phytochemicals, such as antioxidant compounds (Cai, Choi, Lee, Park, & Baik, 2014). For this reason, numerous studies have been conducted to investigate the nutritional quality and health benefits of whole wheat.…”
Section: Introductionmentioning
confidence: 99%
“…Cai et al [10] found that insoluble dietary fiber content of bran exhibited significantly negative relationships with loaf volume of whole wheat bread. Similar to the increase in R value of dough (Figure 1), the mantou with high WWF had higher hardness due to the rigid nature of fiber.…”
Section: Modelmentioning
confidence: 99%
“…Because WWF and bran are rich in fibers, the replacement of wheat flour (WF) by WWF and bran affects the processing condition and quality of pan bread [10,11]. Increasing the amounts of WWF and multigrain led to the increase in farinograph water absorption and the decrease in stability [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation